Boosting electrocatalytic generation of FDCA and H2 from 2,5-furanedimethanol solution by carbonized wood supported Fe-CoP nanoleaves - Yuan Ma; Jiaojiao Miao; Yuanyuan Li; Xuehua Zhou; Lianbing Zhang; Jian Zhang; Guanglei Li; Yong Qin; Jie Gao (Biochar)
Abstract Electrocatalytic oxidation of more stable 2,5-furanedimethanol (FDM) for 2,5-furanediformic acid (FDCA) generation with concurrent hydrogen production is attractive but still nascent compared to 5-Hydroxymethyl-2-furaldehyde (HMF). The need for effective and stable bifunctional electrocatalysts that are efficient for the FDM cell is thus quite significant. Wood serves as an ideal matrix for boosting the performance of catalysts, since its hierarchical porous structures facilitate mass transport and provide abundant active sites. Unfortunately, it has never been demonstrated for electrochemically organic synthesis. Herein, the effectiveness of Fe-CoP in catalyzing FDM oxidation was demonstrated by density functional theory (DFT) calculations and experiments, and a renewable carbonized porous wood decorated with Fe-doped CoP nanoleaves (Fe-CoP/CW) was constructed for electrocatalytic FDCA and hydrogen generation. The obtained Fe-CoP/CW as an anode in FDM solution afforded a current density of 100 mA cm−2 with a yield of 90% FDCA at a potential no more than 1.50 V vs RHE, which was 90 mV and 350 mV lower than Fe-CoP/carbon cloth (CC) and IrO2. In addition, Fe-CoP/CW showed excellent long-term stability for 108-h FDM oxidation in strong alkaline solution. Remarkably, in stark contrast to Fe-CoP/CC and Pt, the hydrogen evolution performance of Fe-CoP/CW was not impacted by FDM at the cathode, and it required exceptionally low overpotentials of 0.19 V to achieve 100 mA cm−2. As a result, in terms of the overall cell, the hydrogen production rate was 0.756 mmol cm−2 h−1, which was 3.57 times higher than those of commonly used commercial Pt | IrO2 cell, presenting a Faraday efficiency of near 100%. This work will pave the way towards the implementation of highly suited bifunctional electrodes and the possibility of affordable, effective, and environmentally-friendly wood-derived electrocatalysts for electrochemically organic synthesis. Graphical Abstract